Inovasi Metode Pembelajaran PAI dalam Meningkatkan Kompetensi Spiritual dan Sosial Siswa di Era Digital - Cantika Amanda Putri Nabilla; Afifah Zahra Fadhilah; Mukmin (JOIES (Journal of Islamic Education Studies), 2025)
This study aims to analyze innovative learning methods in Islamic Religious Education (PAI) that strengthen students’ spiritual and social competencies in the digital era. The research employs a literature review method by examining books, scholarly articles, and reputable online sources published in the last decade. The findings show that digital-based PAI learning encourages interactive, contextual, and collaborative learning through multimedia, gamification, digital literacy, and project-based learning. These innovations are proven to enhance students’ motivation, critical thinking, ethical awareness, and internalization of Islamic values. Furthermore, the study identifies challenges such as digital inequality, low teacher digital literacy, and ethical risks in online interaction, which may hinder students’ spiritual development. The results also highlight the important role of teachers as designers of digital learning who integrate Islamic ethics into learning activities. In conclusion, the study emphasizes that digital innovation in PAI must balance technological advancement with spiritual and moral formation, ensuring that students develop not only digital competence but also strong Islamic character and responsible social behavior.